Konseling Gizi terhadap Pengetahuan Wanita Usia Subur dengan Kekurangan Energi Kronik - Ana Mariza; Mei Lidia Utami; Sunarsih Sunarsih; Rosmiyati Rosmiyati (Universitas Malahayati Lampung, 2025)
ABSTRACT The incidence of chronic energy deficiency (CED) in developing countries such as Bangladesh, India, Thailand, Indonesia, Myanmar, and Sri Lanka ranges from 15% to 47%, indicated by a Body Mass Index (BMI) of less than 18.5%. According to WHO (2018), CED among women of reproductive age (WRA) is one of the causes of 20 million or 15-20% of infants experiencing nutritional problems, such as low birth weight (LBW). A preliminary study conducted in the Bangun Rejo area found that there are still women of reproductive age who appear thin or underweight. The general objective of this study was to determine the effect of nutritional counseling on the knowledge of women of reproductive age with chronic energy deficiency in the working area of Bangun Rejo Primary Health Care, Bangun Rejo District, Central Lampung Regency. The research design used was a One-Group Pretest-Posttest Design, with an experimental type of research and a Pre-Experimental Design form using primary data. The population of WRA with CED in the working area of Bangun Rejo Primary Health Care was 94 people. The research was conducted in July 2024 with 30 respondents, and data collection was carried out using a questionnaire, followed by analysis using a paired t-test in SPSS.Results: The study results showed that the average knowledge level of respondents before receiving nutritional counseling was 50.17. After receiving nutritional counseling, the average knowledge level increased to 82.50. There was a significant effect of nutritional counseling on the knowledge of women of reproductive age with chronic energy deficiency in the working area of Bangun Rejo Primary Health Care, Bangun Rejo District, Central Lampung Regency, with a p-value of 0.000. The conclusion drawn is that there was an increase in the knowledge level before and after counseling, with an average increase of 32.33. It is recommended that respondents continue to improve their knowledge by attending youth health post to further enhance their understanding of CED and health in other adolescents. Keywords: Nutrition, CED, Knowledge, WRA ABSTRAK Kejadian kekurangan energi kronik di Negara-negara berkembang seperti Bangladesh, india, Thailand, Indonesia, Myanmar, dan Srilangka adalah 15%-47% yaitu dengan BMI 18,5%. WHO (2018) mengatakan KEK pada WUS menjadi salah satu penyebab dari 20 juta atau 15-20% bayi mengalami masalah gizi, seperti berat badan lahir rendah (BBLR). Hasil studi pendahuluan di wilayah Bangunrejo masih didapati wanita usia subur yang terlihat kurus atau memiliki berat badan yang rendah. Tujuan penelitian untuk mengetahui Pengaruh konseling gizi Terhadap Pengetahuan Pada Wanita Usia Subur Dengan Kekurangan Energi Kronik di Wilayah Kerja Puskesmas bangunrejo Kecamatan Bangunrejo Kabupaten Lampung Tengah. Metode Penelitian: Desain penelitian dilakukan secara One Group Pretest-Posttest Design dengan jenis penelitian eksperimen dengan bentuk Pre-Experimental Designs menggunakan data primer. Populasi WUS KEK yang ada diwilayah kerja puskesmas Bangunrejo yaitu 94 orang, penelitian Dilakukan pada bulan Juli 2024 terhadap 30 orang responden dengan pengumpulan data menggunakan kuesioner kemudian dianalisa dengan uji paired t-test menggunakan SPSS. Hasil penelitian didapatkan tingkat pengetahuan responden sebelum diberi konseling gizi rata-rata 50,17, Tingkat pengetahuan setelah diberi konseling gizi Tingkat pengetahuan responden rata-rata naik menjadi 82,50, Ada Pengaruh konseling gizi Terhadap Pengetahuan Pada Wanita Usia Subur Dengan Kekurangan Energi Kronik di Wilayah Kerja Puskesmas bangunrejo Kecamatan Bangunrejo Kabupaten Lampung Tengah dengan p value 0,000. Diikuti kesimpulan: Ada kenaikan Tingkat pengetahuan sebelum dan setelah dengan rata-rata sebesar 32,33. Diharapkan bagi responden untuk terus meningkatkan pengetahuannyan dengan cara mengikuti posyandu remaja agar semakin tahu tentang Pengetahuan KEK dan Kesehatan pada remaja lainnya. Kata Kunci: Gizi, KEK, Pengetahuan, WUS